Effectiveness of Learning Videos Using Inshot Application - Luqman MoHa; Ummu Sulaimah Saleh; Panji Prasetya Utama (Yayasan Adra Karima Hubbi, 2023)
Background. Optimizing video-based online media during the covid-19 pandemic for distance learning for students in understanding learning materials to produce optimal value and strong understanding. Purpose. Based on the background and conditions at this time which are still in a pandemic that the learning process is still semi-online, it is hoped that a learning media that is appropriate and effective for sharing student knowledge. error one media that can be used is a learning video. Method. In this study the authors used a type of qualitative research . type of research uses qualitative research with interview methods. This interview method consists of various groups including irregular, non-standard, casual, or focused interviews ranging from ordinary to specialized questions. Semi-structured Interviews. The interview will begin with easy questions about the subject or research we are doing to the interviewees we will ask. Structured or standardized interviews Results. The result of this research is that the effectiveness of using learning video media in elementary school 02 tanjung bonai, north lintau buo sub-district, flat land district is very effective due to an increase in the quality and quality of education in the school. Conclusion. The effectiveness of using learning video media in elementary school 02 tanjung bonai, north lintau buo sub-district, flat land district is very effective due to an increase in the quality and quality of education in the school.